Respiratory gas carriers in plant culture systems - Anthony, Paul (1999)
A crucial pre-requisite in genetically manipulating higher plants involves systems for culturing plant protoplasts and cells under static conditions with an adequate oxygen supply. This is especially the case for cells from cryopreservation, where respiratory perturbations are known to occur during early post-thaw recovery. Therefore, studies were undertaken to assess the potential, and actual, beneficial effects involving culture of cells at an interface between inert, oxygen-gassed perfluorocarbon (PFC) liquid overlaid with liquid or semi-solidified media supplemented with or without the non-ionic surfactant, Pluronic F-68. Assessments were also made to compare the efficacy of PFC supplementation with other physical (medium implanted with glass rods to increase the surface area available for gaseous exchange) and chemical (haemoglobin; Hb) options, both alone and in combination, for gaseous manipulation of plant protoplast cultures.